The effect of aromatherapy with rose essential oil on postpartum blues in primiparous women: A randomized controlled clinical trial - Roya Tabasi; Maryam Moradi; Roshanak Salari; Vahid Ghavami; Negar Asgharipour; Farideh Akhlaghi (Mashhad University of Medical Sciences, 2023)
Introduction: Postpartum blues is a transient period of increased emotional reactivity that occurs in approximately half of women in the first week after delivery. Due to the high prevalence of postpartum blues and its adverse effects on the mother, baby, and the family, as well as the acceptance of complementary medicine and aromatherapy, especially in women, and the sedative effects of rose essential oil, the present study was performed with aim to determine the effect of aromatherapy with the rose essential oil on postpartum blues in primiparous women. Methods: This randomized clinical trial study with a placebo group was conducted in 2022 on 65 primiparous women admitted to Omolbanin Hospital in Mashhad. The data was completed through demographic-obstetrical information form, Stein postpartum blues questionnaire and Rosenberg's social support and self-esteem scale, Paswald scale, and Rothen fatigue intensity scale. Rose essential oil was used in the intervention group, and in the placebo group, sweet almond oil was used in the same way. The postpartum blues scores were measured on the 4th, 10th, and 14th days. Data analysis was done using SPSS statistical software (version 22) and Independent t-test, Man-Whitney, Chi-square and Fisher's exact tests. P<0.05 was considered statistically significant. Results: There was no statistically significant difference between the two groups in terms of the postpartum blues score before the intervention (P=0.246). But after intervention, the postpartum blues score in the intervention group was significantly lower than the placebo group on the 4th, 10th, and 14th days after delivery (P<0.001). Conclusion: Aromatherapy with rose essential oil was effective and safe in reducing postpartum blues in primiparous women.